Value Chain Evolution: Existing Theories, Vision, and Future Trend - Abdullayev Javoxir Jaxongirovich (European Science Publishing, 2024)
This article describes the theories, concepts and views of prominent scientists on the concept of the value chain. In particular, the concept of the value chain and its tasks, theories related to its components, management methods and various criteria for their coordination have been considered in the literature. The article provides information on the interaction of the value chain, the emergence of dynamic relationships between different activities in the structure of the value chain. This article consists of a comprehensive review of research on the value chain, identifying existing problems and shortcomings, and offering new directions for future research.
Keywords: Value, price, value chain, value formation, Global value chain, optimization, supply chain.